Pertumbuhan Stek Batang Nepenthes reinwardtiana Miq. Setelah Direndam Dengan Urin Kambing - Elvi Rusmiyanto Pancaning Wardoyo, Sri Mufiddah, Mukarlina, (Jurnal Protobiont, 2018)
Nepenthes reinwardtiana Miq. is one of the species of Nepenthes found in west Borneo where its population in nature is declining. Ex-situ conservation efforts by cultivating vegetatively through stem cuttings need to be done to overcome the extinction of N.reinwardtiana. One of the factors that determines the growth of cuttings is the content of the external growth regulator namely auxin. One of the sources of organic auxin that can be used is goat urine. This research was conducted to find out the effects of goat urine on the growth of stem cuttings of N.reinwardtiana and to find out the concentration of goat urine that provides the best growth on N.reinwardtiana stem cuttings. The method used is completely randomized design with 4 treatments which is goat urine concentration of 0,15,30 and 40% , each treatment is repeated 3 times so that 12 units of experiment were obtained. The results show that immersion of goat urine has significant effect on the time of shoot, the number of roots and height of the plant but does not provide the number of shoots. Goat urine concentration of 15% produces that fastest shoot growth namely 11.23 days while the concentration of 30% gives the best result on the number of roots as many 2 pieces and the height of the plant namely 4.17 cm.